Konsep Pendidikan Islam Menurut Muhammad NatsirDan Aktualisasinya Dalam Pendidikan Di Indonesia - Lestari, Puspita, Dr. Mohammad Ali, M.Pd (2016)
Discussing the issue of Islamic education means talking about man himself as a creature of God which prepared to be a caliph (leader) on earth in order to serve the God. One of the challenges of Islamic education is still the dichotomy of science. It's meaning, there's a separation between religious sciences and world sciences that get rid of each other. This perspective will obviously have a big impact on one's attitude in looking at science. Based on that point, the author discusses more about thought of figure and Indonesian muslim intellectuals who tried to formulate Islamic education in line with the religion's hope, nation and state, he is Muhammad Natsir. Therefore, the author has taken the title "The Concept of Islamic Education According to Muhammad Natsirand Actualization in Education in Indonesia". This research aims to get information about the concept of Islamic education according to Muhammad Natsir and actualization of his thought in education in Indonesia. This research already use qualitative research methods with type of literature and historical approach. And documentation for method of collecting data, and content analysis for data analysis. By it framework, can be seen that the concept of Islamic education according to Muhammad Natsir is the concept of education that combines between general education and religious education, sustainability is evidenced by not dispute between west and east. Islam only knows the difference between right and falsehood. All the rights are acceptable although coming from the west, and all falsehood will be removed although coming from the east. Therefore, will be create students who are concerned their spiritual and their physical. Actualization of Natsir's thought in education in Indonesia can be seen from the schools that combined between religious sciences and world sciences in the curriculum. At general schools already incorporate Islamic education in a balanced, as well as Islamic schools or boarding schools have entered the national curriculum in a balanced anyway.